2017
DOI: 10.1038/s41598-017-12354-y
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the role of seagrasses in regulating sediment surface elevation

Abstract: Seagrass meadows provide numerous ecosystem services and their rapid global loss may reduce human welfare as well as ecological integrity. In common with the other ‘blue carbon’ habitats (mangroves and tidal marshes) seagrasses are thought to provide coastal defence and encourage sediment stabilisation and surface elevation. A sophisticated understanding of sediment elevation dynamics in mangroves and tidal marshes has been gained by monitoring a wide range of different sites, located in varying hydrogeomorpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(95 citation statements)
references
References 51 publications
3
91
0
1
Order By: Relevance
“…A recent study, encompassing both intertidal and subtidal and tropical and temperate seagrass ecosystems showed that presence of seagrass resulted in an average difference in surface elevation rate of 31 mm/year, compared to adjacent unvegetated sediments (Potouroglou et al, ). Furthermore, although not measured in this study, the structure of seagrass meadows can also be a potentially important predictor for the magnitude and source of seagrass C org stocks.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study, encompassing both intertidal and subtidal and tropical and temperate seagrass ecosystems showed that presence of seagrass resulted in an average difference in surface elevation rate of 31 mm/year, compared to adjacent unvegetated sediments (Potouroglou et al, ). Furthermore, although not measured in this study, the structure of seagrass meadows can also be a potentially important predictor for the magnitude and source of seagrass C org stocks.…”
Section: Discussionmentioning
confidence: 99%
“…). Relative water motion was characterized using the dissolution rates of Plaster of Paris chalk blocks, which integrates the effects of both tidal currents and waves (Potouroglou et al ). We attached preweighed (~ 130 g) plaster blocks to PVC stakes, which were inserted into the sediments such that the blocks were approximately mid‐canopy.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have documented a decline in the extent of seagrasses for many areas worldwide (Cambridge et al, 1986;Campbell & McKenzie, 2004;Cardoso et al, 2004;Daby, 2003;Gonzalez et al, 2005;Hughes et al, 2004;Morris & Viknstein, 2004;Orth et al, 2006;Polte et al, 2005;Short & Burdick, 1996;Waycott et al, 2005). Seagrasses also impact system morphology due to their capacity to hold sediments and favor deposition (Ganthy et al, 2013;Harlin et al, 1982;Potouroglou et al, 2017). For instance, Ganthy et al (2013) studied sediment transport dynamics in tidal flats in the Arcachon lagoon, measured centimeter-scale accretion rates over seagrass meadow, and found that these were correlated with seasonal growth rates.…”
Section: Research Lettermentioning
confidence: 99%